Order Structure of the Figà-Talamanca-Herz Algebra. (30th May 2011) - Shams Yousefi, Marzieh; Amini, Massoud; Sady, Fereshteh
Abstract : We study the interplay between the order structure and thep -operator space structure of Figà-Talamanca-Herz algebraA p (G) of a locally compact groupG . We show that for amenable groups, an order and algebra isomorphism of Figà-Talamanca-Herz-algebras yields an isomorphism or anti-isomorphism of the underlying groups. We also give a bound for the norm of ap -completely positive linear map from Figà-Talamanca-Herz algebra to its dual space.